How suicidal patients shape early career psychotherapists’ experiences of their professional competence : an interpretative phenomenological analysis - Martin, Jarred H. (University of Pretoria, 2024)
Mini Dissertation (MA (Clinical Psychology))--University of Pretoria, 2024.